Aid under fire : nation building and the Vietnam War - Elkind, Jessica Breiteneicher, 1976- (Studies in conflict, diplomacy, and peace., 2016)
"In the aftermath of World War II, as longstanding empires collapsed and former colonies struggled for independence, the US employed new diplomatic tools to counter challenges to its interests across the globe. Among the most important new strategies was development assistance-the attempt to strengthen alliances by providing technology, financial aid, and administrators to fledgling states in order to disseminate and inculcate American practices in local populations. While the US implemented development programs in several nations, nowhere were these policies more significant than in Vietnam. In Aid Under Fire, Jessica Elkind examines US nation-building efforts in the South Vietnamese state during the decade before the ground war. Based on archival sources and interviews with aid workers, this study demonstrates how the official US aid agency as well as several nongovernmental organizations implemented nearly every component of nonmilitary assistance given to South Vietnam, including public and police administration, agricultural development, education, and public health. Despite the sincerity of American efforts, most Vietnamese citizens understood them to be little more than a continuation of attempts by foreign powers to dominate their homeland. Elkind argues that, instead of reexamining their core assumptions or their approach as violence in the region escalated, US policymakers and aid workers only strengthened their commitment to nation building, increasingly modifying their goals to support counterinsurgency efforts. Aid Under Fire highlights the important role played by nonstate actors in advancing US policies and reveals in stark terms the limits of American power and influence during the period widely considered to be the apex of US supremacy in the world"--